Socio-demographic Characteristics of Vesico-vaginal fistula (VVF) patients attended at a tertiary Care Hospital in Bangladesh - Akter, Shimul; Shewly, Naznin Rashid; Khatun, Kashefa; Nupur, Rokshana Parvin; Nahar, Kamrun; Sultana, Nilufar; Sharmin, Farzana (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Vesico-vaginal fistula can occur in different women with varied socio-economic condition. Objectives: The purpose of the present study was to see the socio-demographic characteristics of vesico-vaginal fistula (VVF) patients attended at a tertiary care hospital in Bangladesh. Methodology: This cross-sectional study was carried out from July 2013 to December 2013 for a period of 6 months in the National Fistula Centre in the Department of Obstetrics & Gynaecology at Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh. All patients who underwent surgical repair for iatrogenic VVF in National Fistula Centre of the department of Obstetrics and Gynaecology of Dhaka Medical College Hospital were included in this study. Patients who got themselves admitted to Obstetrics & Gynaecology department of DMCH with the complaints of fistula. The entire selected patients were interviewed for detailed socio-demographic characteristics. Result: A total number of 51 cases of VVF were recruited for this study. The mean age was 46.02 (±SD 6.104) years. Most of the respondents were illiterate (55.0%) and one-third patients had primary level education. The number of highly educated patients was scarce (12.0%). It was evident that average age at marriage of the patients was 15.8(±4.74) years. Some females were forced to accept marriage at the age of 10 years. The mean interval between initiation of menstruation and the marriage was only 4.72 years. Mothers were on an average 17.48 years old at the time of first delivery. Conclusion: In conclusion middle age illiterate women are most commonly suffering from VVF. Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 114-117